EFFECTIVENESS OF THROMBOLYSIS BY NON-IMMUNOGENIC STAPHYLOKINASE IN PATIENT WITH ST-ELEVATION MYOCARDIAL INFARCTION - N. T. Vatutin; V. B. Kostogryz; A. I. Kostogryz; O. A. Polyakova; E. A. Ryabko; O. I. Stolika; A. N. Zagoruyko (Российский кардиологический журнал)
.